Lokalitas Tafsir Nusantara: Dinamika Studi al-Qur’an di Indonesia - Zaiyadi, Ahmad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2018)
Tafsir Nusantara is a manifestation of the assessment and Quranic writing in Nusantara. The arrival of a Al-Qur’an interpretation in Nusantara can not be separated from the process of the assessment and writing it as part of an effort by Ulama’ in understanding and spread the Islamic Teachings. In this context, Locality of the nuance also coloring variety of Quranic interpretation, both in assesment of the Quranic interpretation in mushalla, mosque, and Islamic boarding school and the writing of interpretation by using local symbolic in form like pegon or latin. In other aspect, the contribution of Middle East Ulama influences many Nusantara ulama’s thats makes genealogy of thought that forming a different tendency in each season. This is seem to the figure of Jalaludin As-Suyuti with Tafsir Al-Jalalain in the form of Ijmaly interpretation, very influences on tafsir nusantara’s products in the classic time such as Tarjuman Al-Mustafid writing by Abdur Rauf As-Sinkili. In the modern times, the figure of Muhammad Abduh through his masterpiece Tafsir Al-Manar, by using tahlily method and Adab al-Ijtima’i approach also give very strong influence to the birth of local Ulama’s products. Starting from Tafsir Al-Qur’an Al-Karim by Muhammad Yunus, Tafsir Al-Azhar by Buya HAMKA and Tafsir Al-Misbah by Quraish Shihab also using social approach. Its culmination, when the influence of modern linguistic in the contemporary period with contextual approach like Major Times of Qur’an by Fazlur rahman inspires scholars nusantara’s thought as the figure of Nurcholis Majid who influences of research thematic verses interpretation in islamic universities. Thus, this study will focus on local Ulama interpretation in the dynamics of the Al-Quran study in indonesia that growing now, as was the theme of social includes, terminology of Kafir, Ahlul Kitab and Non-Muslims.